The Effect of Visionary Leadership Managerial Ability and Job Satisfaction on Teacher Performance - Muhammad Taufiq Azhari; Candra Wijaya; Tien Rafida (Journal Evaluation in Education (JEE), 2025)
Purpose of the Study: The study focuses on three key variables: visionary leadership of madrasah principals, managerial ability, and job satisfaction. These variables are explored as internal and institutional factors that shape the meaning of educational quality and directly impact teacher performance. The research aims to determine which of these factors plays the most significant role in enhancing the effectiveness and productivity of certified teachers within the context of Islamic educational institutions. Methodology: This research employs a quantitative survey method to measure respondents’ perceptions and attitudes. It is categorized as confirmatory research, validating existing theoretical models by identifying the most influential variables affecting teacher performance. Additionally, it uses a correlational approach to measure the strength and direction of the relationships between the selected variables and teacher outcomes. A total of 242 respondents were selected using random sampling, and data were analyzed using path analysis to explore both direct and indirect effects. Main Findings: The study reveals that visionary leadership, managerial competence, and job satisfaction all exert significant direct effects on teacher performance. Among them, visionary leadership is identified as the most dominant contributor. Novelty/Originality of the Study: The novelty lies in the simultaneous and integrative investigation of leadership, managerial skills, and job satisfaction within a specific regional and institutional context. Unlike prior studies that often analyze these factors in isolation, this research offers a comprehensive causal model tailored to Madrasah Tsanawiyah Negeri, filling a gap in the literature on Islamic school leadership and performance enhancement.